1999
DOI: 10.1046/j.1365-2141.1999.01542.x
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of central nervous system aspergillosis using polymerase chain reaction, latex agglutination test, and enzyme‐linked immunosorbent assay

Abstract: To investigate the usefulness of examination of cerebrospinal fluids (CSF) in the diagnosis of central nervous system (CNS) aspergillosis, we examined five patients with either brain abscesses or cerebral infarctions and 11 control patients. CSF samples were subjected to enzyme‐linked immunosorbent assay (EIA), latex agglutination test (LA) and polymerase chain reaction (PCR). Cultures of CSF samples were negative in all the patients, but PCR, EIA and LA were positive in five, four and four patients with CNS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 5 publications
0
53
0
2
Order By: Relevance
“…Recently, detection of Aspergillus antigen or DNA in CSF has been suggested to be useful in the diagnosis of CNS aspergillosis. 22 A definitive diagnosis of CNS aspergillosis requires histopathological samples, that can be obtained only by neurosurgery. These procedures are often not practical in this setting and may unnecessarily delay the start of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, detection of Aspergillus antigen or DNA in CSF has been suggested to be useful in the diagnosis of CNS aspergillosis. 22 A definitive diagnosis of CNS aspergillosis requires histopathological samples, that can be obtained only by neurosurgery. These procedures are often not practical in this setting and may unnecessarily delay the start of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated recently that Aspergillus DNA can be detected successfully in various samples by different PCR-assays 7,[9][10][11][12][13][14] . We have evaluated the specificity of determination, sensitivity, repeability Detection of Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…69 Culture of CSF infrequently yields positive results, 94,114 and both chemical findings in the CSF and the CT results are often non-specific. [115][116][117] Galactomannan may also be detected in the CSF, with a sensitivity and specificity of 80% and 100%, respectively, according to a study involving only five patients with proven CNS aspergillosis. 117 Galactomannan has been detected in other clinical specimens as well.…”
Section: N E W D I a G N O S T I C T O O L Smentioning
confidence: 99%
“…[115][116][117] Galactomannan may also be detected in the CSF, with a sensitivity and specificity of 80% and 100%, respectively, according to a study involving only five patients with proven CNS aspergillosis. 117 Galactomannan has been detected in other clinical specimens as well. 69 …”
Section: N E W D I a G N O S T I C T O O L Smentioning
confidence: 99%